Online Self-Regulated Learning Strategies in the Process of Writing Undergraduate Thesis: A Survey Study - Hapsari, Astri; Fatmasari, Tiara Ayu (Journal of English and Education (JEE), 2022)
This survey study aims to identify EFL undergraduate students’ online self-regulated learning strategies in the process of writing their undergraduate theses during COVID-19 pandemic. 97 senior students agreed to participate in this study. This study used a 24-item questionnaire adapted from Barnard et al. (2009) Online Self- Regulated Learning Questionnaire (OSLQ). The results revealed that the participants’ online self-regulated learning strategies in the process of writing their undergraduate theses from the highest to lowest mean score were: environment structuring, help-seeking, self-evaluation, goal setting, time management, and task strategies. Environment structuring had the highest average score, indicating that undergraduate English Education students were able to choose and arrange places for online learning to minimize distractions so that their learning could run optimally. However, the ability of self- regulated learning strategies in the task strategy domain had the lowest average score. The results displays that in the process of writing undergraduate theses, participants’ ability in task strategies needed to be improved. For further research, the researchers recommend further investigation on the relationship between undergraduate students’ motivation and ability in implementing their self-regulated online learning strategies in writing undergraduate thesis. Future research should also include metacognitive learning strategies and re-examine the relationship of undergraduate students’ online self-regulated learning strategies to their online learning performance in writing undergraduate theses.